2001
DOI: 10.1021/om000784p
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Photophysical Reactions of fac-Rhenium(I) Tricarbonyl Complexes. Effects from Binucleating Spectator Ligands on Excited and Ground State Processes

Abstract: Ground and excited state properties of the newly prepared complexes Re(CO) 3 (2,2′-biquinoline)L S + , L S ) pyrazine or 4,4′-bipyridine, and Re(CO) 3 (2,2′-bipy)(2-pyrazinecarboxylate) were investigated by steady state and time-resolved spectroscopy. The X-ray structure of the latter compound showed that the spectator ligand 2-pyrazinecarboxylate is coordinated through the carboxylate group to Re(I). A component of the complexes' luminescence was associated with long-lived Re to ligand, 2,2′-biquinoline or 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(142 citation statements)
references
References 31 publications
(69 reference statements)
10
127
0
5
Order By: Relevance
“…Elemental analyses were obtained by using a Perkin-Elmer 240-B microanalyzer. The IR spectra were recorded on a Perkin-Elmer FT 1720-X spectrophotometer, while the 1 [14] and [Re-(OTf)(CO) 3 (NÀN)] [44] were synthesized according to literature procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analyses were obtained by using a Perkin-Elmer 240-B microanalyzer. The IR spectra were recorded on a Perkin-Elmer FT 1720-X spectrophotometer, while the 1 [14] and [Re-(OTf)(CO) 3 (NÀN)] [44] were synthesized according to literature procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Absorbance changes, DA, occurring on a time scale longer than 15 ns were investigated at r.t. with a flash-photolysis apparatus described elsewhere [31]. In these experiments, 15 ns flashes of 351 nm light were generated with a Lambda-Physik-SLL-200 excimer laser.…”
Section: Experimental Partmentioning
confidence: 99%
“…Interest in the properties that L S imposes on the ÀRe I L A (CO) 3 moiety is brought about by possible applications of the Re complexes to biochemical processes [8 ± 11] and to CO 2 reduction [12]. Also, the derivatization of polymers with chromophores, e.g., with pendant ÀRe I L A (CO) 3 groups [13] has prompted investigation of the role of L S in the reactivity of some Re I monomers [14]. Literature reports show, for example, that the function of L S is to exert small perturbations that alter the electronic structure of the chromophore and modify its photophysics [6].…”
Section: ] àmentioning
confidence: 99%
“…The photophysical and photochemical properties of [Re I (NO 2 Bz)L A (CO) 3 ] [7] and [Re I (pz-2-CO 2 )(2,2'-bipy)(CO) 3 ] ((2,2-bipyridine)tricarbonyl(pyrazine-2-carboxylato)rhenium) [14] have strongly suggested that the carboxylato group electronically insulates the Re I chromophore from the pendant 4-nitrophenyl and pyrazine moieties. In this work, we have studied the photophysics and redox reactivity of the 9,10-dihydro-9,10-dioxoanthracene-2-carboxylate x( anthraquinone-2-carboxylate; aq-2-CO 2 ) and its complex [Re I (aq-2-CO 2 )(2,2'-bipy)(CO) 3 ], to learn how such insulation by the carboxylato group of the ligand affects photoreactions initiated in Re I -to-L A and Re Ito-L S charge-transfer excited states MLCT and intraligand excited states IL.…”
Section: ] àmentioning
confidence: 99%
See 1 more Smart Citation